Gastric extremely well-differentiated intestinal-type adenocarcinoma: a challenging lesion to achieve complete endoscopic resection - Kang, K. J.; Kim, K.-M.; Kim, J. J.; Rhee, P.-L.; Lee, J. H.; Min, B.-H.; Rhee, J. C.; Kushima, R.; Lauwers, G. Y. (Endoscopy, 2012)
Extremely well-differentiated tubular adenocarcinomas (EWDAs) of the stomach are characterized by surface maturation and their mimicking of intestinal metaplasia. Endoscopically, intramucosal EWDAs are frequently ill defined with indistinct borders due to the pallor of the neoplastic mucosa and the lack of contrast against the background atrophic and metaplastic mucosa. We evaluated the effectiveness of endoscopic resection for EWDAs after endoscopic submucosal dissection (ESD).Among 872 patients with early gastric cancer, 17 EWDAs were identified (1.9 %). Endoscopically, the flat or depressed type was significantly more common among EWDAs (88.2 %) than among early gastric cancers of other histologies (37.8 %; P < 0.01). The discrepancy between endoscopically estimated tumor size and tumor size as confirmed in pathology reports was significantly greater among EWDAs (18.4 ± 22.0 mm) than among others (5.8 ± 7.5 mm). Involvement of the lateral resection margin was more common (29.4 % vs. 2.5 %; P < 0.05), and complete resection was achieved less often in EWDAs (47.1 % vs. 80.4 %; P = 0.01) compared to the others.EWDAs are associated with higher rates of incomplete resection after ESD, especially along the lateral margins. Pathologists should alert endoscopists when this diagnosis is made, with its associated risks; and endoscopists should pay particular attention to the extent of these tumors during resection.